IS LEPTIN A DETERMINANT OF BONE MINERAL DENSITY IN POSTMENOPAUSAL WOMEN WITH OSTEOPOROSIS? - Günşah Şahin,; Hayal Güler,; Melek Sezgin,; Gürbüz Polat, (Archives of Rheumatology, 2005)
In this study, we aimed to investigate the serum leptin level whether it is a determinant of bone mineral density (BMD) in osteoporotic postmenopausal women. Forty (40) osteoporotic female patients (screened according to WHO criteria, tscore < 2.5SD, at lumbar region or femoral neck region) and forty (40) age and body mass index matched healthy female subjects(served as control group;t score >-1.0 ) were studied. All the women were at post-menopausal period. Serum concentrations of leptin after an overnight fast were measured by radioimmunoassay. BMD values were measured by dual energy X-ray absorptiometry (DEXA, NORLAND XR-46 ) at the lumbar spine, femoral neck and total body. There was no significant difference between groups regarding serum leptin levels (P=0.599). Our study showed that there was no statistically significant difference concerning serum leptin levels in osteoporotic and non-osteoporotic postmenopausal women . However, at a local tissue level, leptin may effect bone. For this reason, leptin related studies at the bone micro-environment are promising.